Sustainability of vector control strategies in the Gran Chaco Region: Current challenges and possible approaches - Gürtler, R.E. (2009)
Fil:Gürtler, R.E. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.